2022
DOI: 10.1007/s11747-022-00858-7
|View full text |Cite
|
Sign up to set email alerts
|

The value relevance of digital marketing capabilities to firm performance

Abstract: Digital transformation of the marketing organization forces firms to develop new digital marketing capabilities (DMCs) to remain competitive. However, despite considerable academic and managerial interest, the value relevance of DMCs beyond the value achieved through classic marketing capabilities (CMCs) remains unclear. Similarly, research investigating the interaction effect of DMCs and CMCs is scarce. We address both research gaps by drawing on a mixed-methods approach combining in-depth interviews and a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 142 publications
5
54
0
5
Order By: Relevance
“…Our interviews with senior managers indicate that there are several logical reasons behind this significant relationship between the market value and investment in digital technologies. Consistent with previous studies (Homburg & Wielgos, 2022;Van Veldhoven & Vanthienen, 2022), this study has also shown that the first reason is that with the growth of digital technologies, organizations achieve a level of complexity that will cause the competition to be unable to imitate them. This acts as an important strategic flank for organizations to achieve a high level of competitive advantage (Mosca, Gianecchini & Campagnolo, 2021;Thornhill, White & Raynor, 2021;Beugelsdijk, 2022).…”
Section: Resultssupporting
confidence: 90%
“…Our interviews with senior managers indicate that there are several logical reasons behind this significant relationship between the market value and investment in digital technologies. Consistent with previous studies (Homburg & Wielgos, 2022;Van Veldhoven & Vanthienen, 2022), this study has also shown that the first reason is that with the growth of digital technologies, organizations achieve a level of complexity that will cause the competition to be unable to imitate them. This acts as an important strategic flank for organizations to achieve a high level of competitive advantage (Mosca, Gianecchini & Campagnolo, 2021;Thornhill, White & Raynor, 2021;Beugelsdijk, 2022).…”
Section: Resultssupporting
confidence: 90%
“…In addition, RBV research argues that the value created by resources/capabilities can be affected by other resources/capabilities owned by the firm (e.g. Homburg and Wielgos, 2022; Zahoor et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…, 2001). RBV indicates that other resources/capabilities owned by the firm can affect the utilisation of particular resources/capabilities (Homburg and Wielgos, 2022; Zahoor et al. , 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…La transformación digital de la organización de marketing obliga a las empresas a desarrollar nuevas capacidades de marketing digital para seguir siendo competitivas (Homburg & Wielgos, 2022;Iniesta-Alemán et al, 2020). El marketing digital es una apuesta necesaria en tiempos de confinamiento, debido a que las oportunidades de negocio son infinitas, además de el hecho de que nuevos usuarios se hayan unido a la digitalización de las compras ya abre un nuevo mercado, por eso las marcas se ven obligadas a buscar alternativas, lo que por obviedad abre puertas a los profesionales del marketing (Toledo Chambilla, 2021).…”
Section: Caso Chileunclassified